2019
DOI: 10.1039/c8cc08326f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light mediated carbamoyl radical addition to heteroarenes

Abstract: Decarboxylative carbamoylation of heteroarenes using oxamic acids under visible-light irradiation is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 51 publications
1
29
0
2
Order By: Relevance
“…It benefits strongly from the ability to use an unmodified carboxylic acid as a reagent. Landais and co‐workers also showed recently that iodine (III) reagents can allow carbamoylation of heteroarenes using oxamic acids under photoredox conditions …”
Section: Advances In Radical Generation Via Decarboxylationmentioning
confidence: 96%
See 1 more Smart Citation
“…It benefits strongly from the ability to use an unmodified carboxylic acid as a reagent. Landais and co‐workers also showed recently that iodine (III) reagents can allow carbamoylation of heteroarenes using oxamic acids under photoredox conditions …”
Section: Advances In Radical Generation Via Decarboxylationmentioning
confidence: 96%
“…Landais and coworkers also showed recently that iodine (III) reagents can allow carbamoylation of heteroarenes using oxamic acids under photoredox conditions. [46] Several months later,Y ang,Z hang and co-workers showed that as imilar method was effective in the absence of photocatalyst, through ap roposed visible light-promoted homolysis of aphenyliodine (III) dicarboxylate, [47] in asimilar manner to ap rior approach by Antonchick (see Sec-tion 3.1). [48,49] In addition to the carboxylic acid precursors, they make an ice advance in terms of generation method by utilizing oxalates,which are generated in situ by treatment of the alcohol with oxalyl chloride.A ne xample of the latter transformation is shown in Scheme 12.…”
Section: Direct Decarboxylation Of Carboxylic Acidsmentioning
confidence: 99%
“…[46] Einige Monate später berichteten Yang, Zhang und Mitarbeiter, dass eine ähnliche Methode auch in Abwesenheit eines Photokatalysators effektiv ist. [46] Einige Monate später berichteten Yang, Zhang und Mitarbeiter, dass eine ähnliche Methode auch in Abwesenheit eines Photokatalysators effektiv ist.…”
Section: Direkte Decarboxylierung Von Carbonsäurenunclassified
“…[44] Dazu nutzten sie den von Fukuzumi beschriebenen, organischen Photokatalysator Mes-Acr (9-Mesityl-10-Methylacridinium) [45] zur Initiierung der vermutlichen Kettenreaktion (siehe mechanistische Überlegungen Landais und Mitarbeiter konnten kürzlich zudem zeigen, dass Iod(III)-Reagenzien die Carbamoylierung von Heteroarenen mit Oxaminsäure unter Photoredoxbedingungen ermçglichen. [46] Einige Monate später berichteten Yang, Zhang und Mitarbeiter, dass eine ähnliche Methode auch in Abwesenheit eines Photokatalysators effektiv ist. Diese Umsetzung erfolgt über eine durch sichtbares Licht vermittelte Homolyse von Phenyliodo(III)-Dicarboxylat, [47] ähnlich dem zuvor von Antonchick beschriebenen Ansatz (siehe Abschnitt 3.1).…”
Section: Introductionunclassified
“…[13] We used readily available, cheap and stable 4-carbamoyl-1,4-dihydropyridines 1 that, upon single-electron transfer (SET) oxidation, can generate carbamoyl radicals. [14] Thea bility of an ickel catalysts to undergo oxidative addition with aromatic bromides 2 while engaging in radical capture mechanisms secured the formation of the cross-coupled amide products 3. [15] Themethod requires mild reaction conditions and avoids the need for any dehydrating agents.I to ffers aw ide scope allowing the straightforward preparation of secondary and tertiary amides and the direct installation of an amide scaffold within biologically relevant heterocycles.I na ddition, we installed amide functionalities bearing electron-poor amine moieties,w hich would be difficult to prepare with classical dehydrative condensation methods.…”
Section: Introductionmentioning
confidence: 99%